Symptombelastung, Inanspruchnahme des Gesundheitssystems und Todesumstände von Menschen mit Demenz in der letzten Lebensphase: der Bayerische Demenz Survey (BayDem) - Kratzer, André; Karrer, Linda; Dietzel, Nikolas; Wolff, Franziska; Hess, Manuela; Kolominsky-Rabas, Peter; Grässel, Elmar (Gesundheitswesen, 2020)
Background Dementia is usually a life-limiting disease. However, evidence-based guidelines for palliative care for people with dementia (PwD) are currently lacking. One reason for this is the dearth of reliable empirical data on PwD at the end of life. The aim of this study is to describe the symptom burden, causes of death, places of death and the use of various health services for PwD at the end of life. Methods The Bavarian Dementia Survey (BayDem) was a multi-center, longitudinal study at 3 different sites in Bavaria, Germany (Dachau, Kronach, Erlangen). Participants were PwD defined by ICD-10 and their informal caregivers. Data were collected in standardized face-to-face interviews in cooperation with local actors. In order to obtain comparable groups, deceased and non-deceased PwD were matched using 1:1 propensity score matching. For the statistical analyses, McNemar tests as well as paired t-tests were used. Results In this analysis, 58 deceased and 58 non-deceased PwD were studied (n=116). In most cases, PwD died at home (36.2%), in hospital (25.9%) or in a nursing home (19.0%), but no one in palliative care. The most common causes of death were respiratory (13.8%) and cardiovascular complications (12.1%) as well as stroke (12.1%). PwD at the end of life showed more pronounced physical comorbidities than the other PwD (Charlson-Index: M=2.75 vs. M=1.80; p=0.030, Cohen's d=0.425) and were therefore admitted to hospital (46.6 vs. 12.1%, p<0.001, OR=6.250) or emergency departments (22.4 vs. 3.4%, p=0.007, OR=6.500) more frequently. Behavioral and psychological symptoms were very pronounced (NPI Score: M=31.67 vs. M=24.77, p=0.118, Cohen's d=0.303). Nevertheless, the utilization of outpatient health services was low. Conclusion The results underline the need to develop evidence-based guidelines to provide palliative care specifically adapted to the needs of PwD at the end of life. In this context, the high incidence of behavioral and psychological symptoms should be taken into account, as should the high incidence of physical comorbidities. Considering the frequent hospital admissions, special attention should also be paid to the development of recommendations for the inpatient sector (acute hospital and palliative care unit).
CRIS-Team Scopus Importer:2020-02-04
Keywords: Death; Dementia; End of life; Palliative care; Symtom burden; Utilization